A Randomized Controlled Trial to Evaluate the Effect of Pulsed Radiofrequency as a Treatment for Anterior Cutaneous Nerve Entrapment Syndrome in Comparison to Anterior Neurectomy. Issue 7 (19th July 2019) - Maatman, Robbert C.; van Kuijk, Sander M.J.; Steegers, Monique A.H.; Boelens, Oliver B.A.; Lim, Toine C.; Scheltinga, Marc R.M.; Roumen, Rudi M.H.
Abstract: Background: Chronic abdominal pain can be due to entrapped intercostal nerves (anterior cutaneous nerve entrapment syndrome [ACNES]). If abdominal wall infiltration using an anesthetic agent is unsuccessful, a neurectomy may be considered. Pulsed radiofrequency (PRF) applies an electric field around the tip of the cannula near the affected nerve to induce pain relief. Only limited retrospective evidence suggests that PRF is effective in ACNES. Methods: A multicenter, randomized, nonblinded, controlled proof‐of‐concept trial was performed in 66 patients. All patients were scheduled for a neurectomy procedure. Thirty‐three patients were randomized to first receive a 6‐minute cycle of PRF treatment, while the other 33 were allocated to an immediate neurectomy procedure. Pain was recorded using a numeric rating scale (NRS, 0 [no pain] to 10 [worst pain possible]). Successful treatment was defined as >50% pain reduction. Patients in the PRF group were allowed to cross over to a neurectomy after 8 weeks. Results: The neurectomy group showed greater pain reduction at 8‐week follow‐up (mean change from baseline −2.8 (95% confidence interval [CI] −3.9 to −1.7) vs. −1.5 (95% CI −2.3 to −0.6); P = 0.045) than the PRF group. Treatment success was reached in 12 of 32 (38%, 95% CI 23 to 55) of the PRF group and 17 of 28 (61%, 95% CI 42 to 72) of the neurectomy group ( P = 0.073). Thirteen patients were withdrawn from their scheduled surgery. Adverse events were comparable between treatments. Conclusions: PRF appears to be an effective and minimally invasive treatment option and may therefore be considered in patients who failed conservative treatment options before proceeding to a neurectomy procedure. Anterior neurectomy may possibly lead to a greater pain relief compared with PRF in patients with ACNES, but potential complications associated with surgery should be discussed.